The Effect of Traditional Jump Rope Games on Leg Muscle Strength of Elementary Students - Hani Choerunisa; Rahmat Permana; Anggia Suci Pratiwi (BASICA, 2026)
This study aims to examine the effect of jump rope on leg muscle strength in physical education classes for sixth-grade elementary school students. Traditional games are movement-based activities designed to support students' physical development through active participation. A quantitative approach with a quasi-experimental nonequivalent control group design was used in this study. Participants were sixth-grade students divided into an experimental group (n = 23) and a control group (n = 24). The experimental group received physical education through the traditional jump-rope game, while the control group received conventional instruction. Before the analysis, normality and homogeneity tests were conducted to determine the appropriate statistical procedure. Leg muscle strength was measured using a vertical jump test administered at the pretest and posttest. Data analysis focused on group differences using the Mann–Whitney test on change scores (posttest–pretest). The Mann–Whitney test results showed a U value of 176,000, Z = -2.279, and a p-value of 0.023 (< 0.05), confirming a significant difference between the experimental and control groups. These findings indicate that the traditional jump-rope game is effective at increasing leg muscle strength. This study was limited to leg muscle strength; further research could explore the broader impact on other motor skills and across different educational contexts.